On three endemic species of the linyphiid spider genus Canariphantes Wunderlich, 1992 (Araneae, Linyphiidae) from the Azores archipelago - Crespo, Luís Carlos; Bosmans, Robert; Cardoso, Pedro; Borges, Paulo A.v. (Zootaxa, 2014)
We describe Canariphantes junipericola n. sp. and C. relictus n. sp., new single-island endemic linyphiid spiders from the islands of Flores and Santa Maria (Azorean archipelago, Macaronesia), respectively. The female of the first species was incorrectly assigned to Canariphantes acoreensis (Wunderlich, 1992), a species occurring in four islands in the Central Group of Azores (Faial, Pico, São Jorge and Terceira). The latter species is transferred to Canariphantes, its male redescribed and the female genitalia described for the first time. We discuss the systematic affinities of these new species and comment on their conservation status.